Gonadal and uterine function in female survivors treated by chemotherapy, radiotherapy, and/or bone marrow transplantation for childhood malignant and non‐malignant diseases. (24th March 2014) - Beneventi, F; Locatelli, E; Giorgiani, G; Zecca, M; Locatelli, F; Cavagnoli, C; Simonetta, M; Bariselli, S; Negri, B; Spinillo, A
<x xml:space="preserve">Abstract</x> Objective To evaluate gonadal function and uterine volume in a cohort of female survivors treated by chemotherapy, radiotherapy, and/or stem cell transplantation (SCT) for childhood malignant and non‐malignant diseases. Design An observational study. Setting S. Matteo Hospital, Pavia, Italy. Population A cohort of 135 female survivors. Methods A clinical, hormonal, and ultrasonographic evaluation. Thirty‐three patients (24%) had non‐malignant haematologic diseases (thalassaemia or sickle cell anaemia), 68 (50%) had leukaemia, 23 (17%) had lymphomas, and 11 (8%) had solid tumours. In total, 106 patients had received SCT, preceded by a conditioning regimen. Main outcome measures Anti‐Müllerian hormone (AMH) and Inhibin–B, and uterine volume. Results The median concentrations of AMH and Inhibin–B in the entire cohort were 0.12 ng/ml (interquartile range, IQR, 0.1–0.5 ng/ml) and 3.5 pg/ml (IQR 0.1–13.2 pg/ml), respectively. In a stepwise ordered logistic regression analysis, conventional chemotherapy for the treatment of malignancies, as opposed to total body irradiation (TBI), was the only oncologically significant predictor of increased AMH levels (OR 4.8, 95% CI 1.9–12, P < 0.001). Conditioning treatment before or after menarche did not influence AMH concentrations (P = 0.24). The best predictor of reduced uterine volume was TBI during the preparation for the allograft (OR 3.5, 95% CI 1.4–8.4, P = 0.006). Increasing age at treatment (OR 0.86, 95% CI 0.77–0.95, P = 0.04), chemotherapy, as opposed to other treatments (OR 0.09, 95% CI 0.03–0.28, P < 0.001), and solid tumours as opposed to either leukaemia/lymphomas or non‐malignant diseases (OR 0.2, 95% CI 0.07–0.56, P = 0.002) were associated with larger uterine volumes. Conclusions Conditioning therapies for SCT, including TBI, had the worst effects on uterine volume and gonadal reserve. Increasing age at treatment and conventional chemotherapy were associated with less detrimental effects on uterine volume.